Effect of Atmospheric-Pressure Plasma on Functional Compounds and Physiological Activities in Peanut Shells - Narae Han; Jinwoo Kim; Jin Hee Bae; Mihyang Kim; Jin Young Lee; Yu-Young Lee; Moon Seok Kang; Duksun Han; Sanghoo Park; Hyun-Joo Kim (MDPI AG, 2022)
Peanut (Arachis hypogaea L.) shell, an abundant by-product of peanut production, contains a complex combination of organic compounds, including flavonoids. Changes in the total phenolic content, flavonoid content, antioxidant capacities, and skin aging-related enzyme (tyrosinase, elastase, and collagenase)-inhibitory activities of peanut shell were investigated after treatment in pressure swing reactors under controlled gas conditions using surface dielectric barrier discharge with different plasma (NOx and O3) and temperature (25 and 150 °C) treatments. Plasma treatment under ozone-rich conditions at 150 °C significantly affected the total phenolic (270.70 mg gallic acid equivalent (GAE)/g) and flavonoid (120.02 mg catechin equivalent (CE)/g) contents of peanut shell compared with the control (253.94 and 117.74 mg CE/g, respectively) (p < 0.05). In addition, with the same treatment, an increase in functional compound content clearly enhanced the antioxidant activities of components in peanut shell extracts. However, the NOx-rich treatment was significantly less effective than the O3 treatment (p < 0.05) in terms of the total phenolic content, flavonoid content, and antioxidant activities. Similarly, peanut shells treated in the reactor under O3-rich plasma conditions at 150 ℃ had higher tyrosinase, elastase, and collagenase inhibition rates (55.72%, 85.69%, and 86.43%, respectively) compared to the control (35.81%, 80.78%, and 83.53%, respectively). Our findings revealed that a reactor operated with O3-rich plasma-activated gas at 150 °C was better-suited for producing functional industrial materials from the by-products of peanuts.